A self-hydrosilylation of phosphanylhydrosilylalkynes promoted by B(C6F5)3? An experimental and mechanistic study. Issue 10 (16th January 2019) - Huang, Yanting; Wang, Xiaoping; Li, Yan; Yang, Ming-Chung; Su, Ming-Der; Zhu, Hongping
Abstract : Reaction of phosphanylhydrosilylalkyne with tris(pentafluorophenyl)borane occurs by the intramolecular hydrosilylation between the Si-centered geminal H and CC functionalities along with the bonding of the borane or boryl group to produce ( E )- and ( Z )-alkenes. Abstract : Phosphanylhydrosilylalkynes Me2 HSiCCPAr2 (Ar = Ph, 1a ; 4-MeC6 H4, 1b ) were synthesized, which reacted with B(C6 F5 )3 to produce alkenes [( E )-(C6 F5 )3 BCHC(PAr2 )SiMe2 ]2 (2a and2b ) and ( Z )-(C6 F5 )2 BCHC(PAr2 )SiMe2 (C6 F5 ) (3a and3b ). The formation of2a (or2b ) involved a Wrackmeyer's SiHMe2 migration followed by Si–H addition across the CC bond, whereas, that of3a (or3b ) involved a similar mechanism with a further C6 F5 migration. The B(C6 F5 )3 -promoted reaction of the Si-centered geminal H and CC groups is thus realized, which may be considered as a self-hydrosilylation. Mechanistic studies by both variable temperature NMR spectroscopy and DFT calculations were accomplished.